STRATEGI NAFKAH RUMAH TANGGA PETANI PEMILIK LAHAN DALAM MENGHADAPI KRISIS BANJIR DI NAGARI DESA BARU BARAT KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - Desfitra Dewi Putri; Irwan; Sri Rahmadani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the livelihood strategies of land-owning farmer households in facing recurrent flood crises in Nagari Desa Baru Barat, Ranah Batahan District, West Pasaman Regency. Repeated flooding has led to damaged rice fields, crop failure, and declining household income, increasing farmers’ economic vulnerability. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving land-owning farmers affected by floods. The findings indicate that flooding directly reduces rice production and destabilizes household income. To cope with these conditions, farmer households adopt several livelihood strategies: adjusting planting schedules and improving irrigation management, diversifying income sources outside agriculture, and utilizing loans for land recovery and farm continuity. These strategies reflect economic adaptation to environmental pressures and disaster risks.